The State and Employers' Associations in British Columbia: 1900-1932 - Yarmie, Andrew (Labour / Le Travail, 2000)
Examines the complexity of capital, state, and labor relations during the early 20th century through a case study of British Columbia employers' associations. To evaluate the sources of employers' strength and to determine the restrictions placed on their dominance, this study uses current theories of the state as a framework. They provide opportunities to examine British Columbia's government as either a "captive state," in a position of relative autonomy, or autonomous. No single theory explains the events of this period. In some sectors of the economy, employers were able to control state policy, but the contradictions created by the state's two primary objectives of capital accumulation and legitimation insured that it would take steps to retain its autonomy in order to maintain capitalist class institutions.